Analysis of the Stability of Russian Banks and the Banking System in the Context of International Sanctions - Denis DOMASCHENKO; Irina PESCHANSKAYA; Irina GUSEVA (Communications of International Proceedings, 2021)
International economic sanctions imposed by a number of Western countries on doing business with individual Russian banks lead to a change in the configuration of banking activities and a shift in the priorities of its development. The authors investigated changes in the economic behavior of each Russian bank under sanctions and identified the features of neutralizing these problems. The general conclusion was the reorientation of resource sources from the international market to the domestic Russian one. Apart from that, additional support to these banks was provided at the expense of moral administrative resources on the part of state authorities, and the entire banking system due to additional injections into bank capital. As a result, the triggered risk of sanctions for most banking entities did not lead to any serious difficulties in running their business, and thus the model of sanctions related to restrictions on access to the international capital market failed to cause delays in their development, but on the contrary, stimulated the search for new internal sources.
Keywords: Banks Under Sanctions; The International Interbank Market; Bank Stability.